1969
DOI: 10.12669/pjms.302.4396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin on Placental, Fetal and Maternal Outcomes in Gestational Diabetes Mellitus

Abstract: Objective:To observe the effects of exogenous insulin on placental, fetal and maternal outcomes in Gestational Diabetes Mellitus (GDM). Methods: After screening and diagnoses(WHO criteria) 30 GDM patients(Group A) were kept on diet control and 39 GDM (Group B) who did not achieve glycemic targets were added subcutaneous insulin. Term placental weight, size, shape, consistency, fibrinoid necrosis, hemorrhages, cord color, length of the cord, completeness of membranes, weight and condition of baby and mode of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 2 publications
0
29
0
2
Order By: Relevance
“…Current therapy given to pregnant women with hyperglycemia include insulin therapy or an oral antidiabetic agents such as glyburide and metformin [19]. Studies have shown various placental, fetal and maternal changes in GDM patients treated with either insulin or oral antidiabetic agents [19][20][21]. For instance, babies borne from GDM mothers who had exogenous insulin are heavier compared to diet controlled GDM mothers, and increased fetal weights have been associated with adverse fetal and maternal outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current therapy given to pregnant women with hyperglycemia include insulin therapy or an oral antidiabetic agents such as glyburide and metformin [19]. Studies have shown various placental, fetal and maternal changes in GDM patients treated with either insulin or oral antidiabetic agents [19][20][21]. For instance, babies borne from GDM mothers who had exogenous insulin are heavier compared to diet controlled GDM mothers, and increased fetal weights have been associated with adverse fetal and maternal outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown various placental, fetal and maternal changes in GDM patients treated with either insulin or oral antidiabetic agents [19][20][21]. For instance, babies borne from GDM mothers who had exogenous insulin are heavier compared to diet controlled GDM mothers, and increased fetal weights have been associated with adverse fetal and maternal outcomes [20]. Another study where the use of metformin was compared with insulin therapy, their meta-analysis resulted to metformin being comparable with the effects of insulin and with less adverse neonatal outcomes and more benefits to the mother such as inhibition of abnormal maternal weight gain [21].…”
Section: Discussionmentioning
confidence: 99%
“… 15 Other studies have suggested IR developing as early as in utero 29 as a result of overproduction of fetal insulin in response to circulating maternal glucose crossing the placenta. 30 The fetus then stores this surplus energy as fat and can result in perinatal complications such as LGA. 18 Given these two trends and the link between the hyperglycaemic intrauterine environment and fetal overnutrition, 19 31 32 women with TIDM belonging to higher BMI subgroups, who exceed IOM guidelines for GWG, may be at the greatest risk of LGA.…”
Section: Introductionmentioning
confidence: 99%
“…Consequences of GDM faced by mother are more chance to develop excessive weight, preeclampsia, undergo cesarean delivery, development of Type 2 diabetes in later in the life (Arshad et al, 2014), hypertensive disorder (Joffe et al, 2008), pregnancy induced hypertension, recurrent vaginal infections (Tamas and Kerenyi, 2000). Difficulties of GDM run into in newborns for example, more birth weight, respiratory distress syndrome (RDS), hypoglycemia, hyperbilirubinemia, polycythemia, hypocalcaemia, congenital anomalies, intrauterine deaths, still births (Arshad et al, 2014), tetany, juandice (Tamas and Kerenyi, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties of GDM run into in newborns for example, more birth weight, respiratory distress syndrome (RDS), hypoglycemia, hyperbilirubinemia, polycythemia, hypocalcaemia, congenital anomalies, intrauterine deaths, still births (Arshad et al, 2014), tetany, juandice (Tamas and Kerenyi, 2000). In pregnancy with GDM, the fetus is exposed to high level of glucose which results in excess fetal growth, impaired insulin secretion and decreased insulin sensitivity (Crowther et al, 2005), the short term complications are shoulder dystocia and infant hypoglycemia (Ferrara et al, 2009), type 2 diabetes mellitus and obesity are the possibility for neonates whose mothers with GDM (Declercq et al, 2007).…”
Section: Introductionmentioning
confidence: 99%